Franjeweverij; het knopen van franjes. Kopie van exemplaar van Dir. Gen. van den Arbeid, Den Haag, nr. 8436
Franjeweverij; het knopen van franjes. Kopie van exemplaar van Dir. Gen. van den Arbeid, Den Haag, nr. 8436.